2016
DOI: 10.1016/j.bbrc.2015.11.060
|View full text |Cite
|
Sign up to set email alerts
|

The role of Wnt regulation in heart development, cardiac repair and disease: A tissue engineering perspective

Abstract: Wingless-related integration site (Wnt) signaling has proven to be a fundamental mechanism in cardiovascular development as well as disease. Understanding its particular role in heart formation has helped to develop pluripotent stem cell differentiation protocols that produce relatively pure cardiomyocyte populations. The resultant cardiomyocytes have been used to generate heart tissue for pharmaceutical testing, and to study physiological and disease states. Such protocols in combination with induced pluripot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 71 publications
(71 reference statements)
1
39
0
Order By: Relevance
“…As a result, the further activation of JNK signaling under 25% with inhibited Piezo1 indicates that the cardiomyocytes might be under mechanical overloading ( Figure 3 C). Consistent with Pahnke A. et al review in which the Wnt activation is reported to be involved in cardiac development, repair, and disease [ 26 ]. Mechanistically, the Wnt binds to receptor Frizzled (Frz), as well as low-density lipoprotein receptor-related protein 5 or 6 (LRP5/6) to stabilize cytosolic β-catenin through glycogen synthase kinase 3 (GSK-3) inhibition.…”
Section: Discussionsupporting
confidence: 78%
“…As a result, the further activation of JNK signaling under 25% with inhibited Piezo1 indicates that the cardiomyocytes might be under mechanical overloading ( Figure 3 C). Consistent with Pahnke A. et al review in which the Wnt activation is reported to be involved in cardiac development, repair, and disease [ 26 ]. Mechanistically, the Wnt binds to receptor Frizzled (Frz), as well as low-density lipoprotein receptor-related protein 5 or 6 (LRP5/6) to stabilize cytosolic β-catenin through glycogen synthase kinase 3 (GSK-3) inhibition.…”
Section: Discussionsupporting
confidence: 78%
“…These highly proliferative cells form the second heart field and are tightly regulated by Wnt2 via the β -catenin pathway ( Tian et al, 2010 ; Norden and Kispert, 2012 ; Ruiz-Villalba et al, 2016 ). Removal of the β -catenin resulted in a reduction of cells within SHF with subsequent aberrant development of the right ventricle and outflow tract ( Klaus et al, 2007 ; Pahnke et al, 2016 ).…”
Section: Wnt Signaling In Cardiac and Vascular Developmentmentioning
confidence: 99%
“…Many of the molecular mechanisms involved in the regulation of EndMT and angiogenesis remain unknown. Nevertheless, we know that the activity of several molecules, including NRP1 (Oh et al, 2002;Matkar et al, 2016), SNAI1 (Sun et al, 2018), SNAI2 (Welch-Reardon et al, 2015),n WNT5b (Wang et al, 2017a), and WNT7a (Howe et al, 2003;Pahnke et al, 2016) induce both EC activation and EndMT. Furthermore, TWIST1 (Mammoto et al, 2018), ZEB1 (Sanchez-Tillo et al, 2010), and ZEB2 (DaSilva-Arnold et al, 2018) induce EndMT and are not known to be involved in EC activation during angiogenesis.…”
Section: The Model As Theoretical Frameworkmentioning
confidence: 99%